Effect of high loading rate and low temperature on mode I fracture toughness of ductile polyurethane adhesive. Issue 1 (2nd January 2019) - Jia, Zhemin; Yuan, Guoqing; Hui, David; Feng, Xiaoping; Zou, Yun
Abstract: The mode I fracture toughness of an adhesive at low temperatures under high loading rates are studied experimentally. Typical R-curves of the polyurethane adhesive under different loading rates (0.5 mm/min, 50 mm/min, 500 mm/min) at different temperatures (room temperature, −20 °C, −40 °C) respectively are obtained. From the experimental results, the mode I fracture toughness of this adhesive is extremely sensitive to the high loading rates and low temperatures. With the increase of the loading rate and decrease of temperature, the mode I fracture toughness of this adhesive decreases significantly. Under the loading rate of 500 mm/min at −40 °C, the mode I fracture toughness of adhesive is 15% of the value at room temperature (RT) under quasi-static conditions. Through the experiment, the relationship between mode I fracture toughness of this adhesive, nominal strain rate and temperature is obtained.